Abstract 13204: Single-Nucleus Multiomic Analyses Identifies Gene Regulatory Dynamics of Phenotypic Modulation in Human Aneurysmal Aortic Root - Zeng, Qingyi; Liu, Xuanyu; Zhou, Zhou (Circulation (New York, N.Y.), 2023)
Introduction: Aortic root aneurysm is a potentially life-threatening condition because it may lead to aortic rupture. However, a single-nucleus transcriptomic and epigenomic landscape in the aortic root tissue of humans is lacking, and the regulatory mechanism of pathogenesis in aneurysmal aortic root remains elusive. We sought to identify molecular triggers for aortic root aneurysm in Marfan syndrome patients. Methods: Aneurysmal aortic root tissues from MFS patients (n=6) and normal aortic root tissues from age-matched, heart transplantation recipients (n=6) were collected. Samples from four subjects of each group were individually subjected to single-nucleus multiomic sequencing (gene expression and chromatin accessibility). Spatial transcriptomic assays were applied to aortic root tissue sections from two subjects of each group. Results: The single-nucleus dataset revealed three subclusters for the vascular smooth muscle cells (VSMCs) lineage including contractile VSMC1 (expressed a high level of RYR2), modulated VSMC2 and VSMC3(expressed a high level of CFH). Statistically significant expansion of the modulated VSMCs was observed in MFS patients. In addition, the modulated VSMCs are not only associated with the diseased states but also associated with the spatial location. The modulated VSMCs are preferentially located in the inner layer of the tunica media close to the intima in both healthy and diseased conditions. Based on the evidence from comparative analyses, we obtained 11 candidate key regulators (such as FOXN3, TEAD1, and BACH1) that potentially drive the phenotypic modulation of VSMCs and the pathogenesis of aortic root aneurysms. The experimental evidence supporting that the forkhead transcription factor FOXN3 may function as a key regulator for maintaining the contractile phenotype of human aortic VSMCs, whose expression decreased during phenotypic modulation and was downregulated in MFS VSMCs. Conclusions: We present the first atlas of gene expression and chromatin accessibility in human aortic root tissue at single-nucleus and spatial resolution. FOXN3 was identified as a novel key regulator for maintaining the contractile phenotype of human aortic VSMCs, which may serve as a potential therapeutic target.